Moringa oleifera aqueous seed extracts and its efficacy in the management of heat stress: assessment of physiological parameters in female New Zealand White rabbits - Valence B. Mutwedu; Albert W. Nyongesa; Rodrigue B. B. Ayagirwe (Discover Animals)
Abstract The present study investigated the efficacy of Moringa oleifera aqueous seed extract (MOASE) on some internal organ weights, hematological and biochemical parameters, oxidative stress biomarkers and kidney histology in female rabbits exposed to heat stress. Twenty-eight New Zealand white female rabbits aged 6 months old and weighing between 2015.6 and 2322.7 g were randomly assigned to four groups according to temperature, relative humidity, temperature and humidity index (THI) and MOASE defined as follows: T0: room temperature (18–24 °C), relative humidity (59 ± 0.48%), and 23.6 ± 1.52 as THI. T1, T2, and T3 had same experimental set-up: 35–36 °C, 64 ± 0.6%, and 32.5 ± 0.7 but additionally co-treated with 100, 200, and 0 mg/kg b.w. MOASE, respectively. Heat was induced in each rabbit cage, using electrical heaters from 08:00 a.m to 4:00 p.m. Skin and rectal temperatures were daily recorded. At 80 day of experimental period animals were sacrificed, blood samples and vital organs collected for appropriate analysis. We report that animals of T1, T2 and T3 significantly increased (P < 0.05) their rectal and skin temperatures, relative weight of lung, kidney and liver. An increase in mean cell volume, white blood cells and lymphocytes followed by an increase in creatinine, urea, alanine aminotransferase, aspartate aminotransferase contents and malondialdehyde were observed in animals at T1, T2 and T3. However, all these parameters decreased in a dose-dependent manner following MOASE administration for each case. A decrease in ovary relative weight, hemoglobin and Red Blood Cells, glucose, blood and kidney protein followed by a decrease in catalase, superoxide dismutase and glutathione peroxidase content for animals at T1, T2 and T3. These parameters increased with the administration of MOASE. Kidney histology of animals at T0 and T2 showed normal similar structures in opposition to the other treatments where abnormalities were observed. Conclusively, administration of MOASE at 200 mg/kg b.w mitigated the physiological disturbances occasioned by heat stress in female rabbits.